Quadruplexes of human telomere dG(3)(TTAG(3))(3) sequences containing guanine abasic sites - Školáková, Petra; Bednářová, Klára; Vorlíčková, Michaela; Sagi, Janos (Biochemical and biophysical research communications, 2010)
This study was performed to evaluate how the loss of a guanine base affects the structure and stability of the three-tetrad G-quadruplex of 5'-dG(3)(TTAG(3))(3), the basic quadruplex-forming unit of the human telomere DNA. None of the 12 possible abasic sites hindered the formation of quadruplexes, but all reduced the thermodynamic stability of the parent quadruplex in both NaCl and KCl. The base loss did not change the Na(+)-stabilized intramolecular antiparallel architecture, based on CD spectra, but held up the conformational change induced in dG(3)(TTAG(3))(3) in physiological concentration of KCl. The reduced stability and the inhibited conformational transitions observed here in vitro for the first time may predict that unrepaired abasic sites in G-quadruplexes could lead to changes in the chromosome's terminal protection in vivo.
Keywords: G-kvadruplexy; Circular Dichroism; konformace nukleové kyseliny; Humans; sekvence nukleotidů; G-Quadruplexes; Nucleic Acid Conformation; Potassium; Guanine; draslík; Sodium; telomery; sodík; Base Sequence; Telomere; cirkulární dichroismus; lidé; guanin